The Effect of Management Changes, Audit Fees, and Return on Assets Percentage Changes on Auditor Switching: A Study of Banking Companies Listed on the Indonesia Stock Exchange (2018–2024) - Rifka Khairunnisa; Abdul Pattawe; Tenripada (Journal GoodWill, 2025)
This study investigates the effect of management changes, audit fees, and percentage changes in return on assets (ROA) on auditor switching in banking companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2024 period. Auditor switching is a strategic decision that may be influenced by both internal corporate factors and regulatory requirements. Using a quantitative verification approach, the study analyzes 70 firm-year observations selected through purposive sampling. Logistic regression analysis was employed to examine whether the three independent variables significantly affect the likelihood of voluntary auditor switching. The empirical results show that management changes, audit fees, and ROA percentage changes do not have a statistically significant effect on auditor switching. These findings indicate that internal managerial or financial fluctuations are not sufficient reasons for banking companies to replace their auditors. The tendency of the banking sector to maintain auditor continuity is closely associated with strict regulations, long-term audit engagement practices, and the industry’s need to uphold credibility, transparency, and stakeholder trust. This study contributes to existing literature by providing evidence that factors influencing auditor switching may be industry-specific, particularly in regulated sectors such as banking. Future research is recommended to incorporate additional variables such as audit tenure, auditor reputation, ownership structure, corporate governance, and financial distress, as well as to compare auditor switching behavior across multiple industries or jurisdictions.